2006
DOI: 10.1103/physrevlett.96.055505
|View full text |Cite
|
Sign up to set email alerts
|

Are the Structures of Twist Grain Boundaries in Silicon Ordered at 0 K?

Abstract: Contrary to previous simulation results on the existence of amorphous intergranular films at high-angle twist grain boundaries (GBs) in elemental solids such as silicon, recent experimental results imply structural order in some high-angle boundaries. With a novel protocol for simulating twist GBs, which allows the number of atoms at the boundary to vary, we have found new low-energy ordered structures. We give a detailed exposition of the results for the simplest boundary. The validity of our results is confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
88
1
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(91 citation statements)
references
References 18 publications
1
88
1
1
Order By: Relevance
“…To find the ground state interface configuration, vacancies and interstitials must be iteratively added until no negative formation energy sites remain. Using this approach or related ones, the ground states of some interfaces have been shown to have local densities and compositions markedly different from the neighboring crystals [8,37,45,46]. In the interface studied here, however, no negative vacancy or interstitial formation energy sites were found.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…To find the ground state interface configuration, vacancies and interstitials must be iteratively added until no negative formation energy sites remain. Using this approach or related ones, the ground states of some interfaces have been shown to have local densities and compositions markedly different from the neighboring crystals [8,37,45,46]. In the interface studied here, however, no negative vacancy or interstitial formation energy sites were found.…”
mentioning
confidence: 81%
“…No such delocalization occurs in Cu-NbSPD: vacancies and interstitials absorbed at misfit dislocations in this interface remain compact, just like conventional point defects in crystalline solids. Second, similar to certain grain boundaries in semiconductors [45,46] and ceramics [60], Cu-NbMSP contains constitutional vacancies. Such vacancies are thermodynamically stable even at zero temperature because they are an intrinsic feature of the ground state interface configuration.…”
Section: Discussionmentioning
confidence: 99%
“…Similar algorithms have been used to reduce GB and heterophase interface energies by removing or adding atoms [30,43]. Indeed, our algorithm provides an effective way of finding low-energy GB structures, which approximate the thermal equilibrium state of well-relaxed boundaries at low temperature.…”
Section: Motivationmentioning
confidence: 99%
“…Using a method for grand-canonical simulated quenching (GCSQ), Phillpot and Rickman found that GB energies may be reduced by removing atoms [28,29]. Similarly, Von Alfthan and Sutton [30] showed that finding the lowest energy states of general GBs in Si often requires removing or adding atoms. Bai et al studied loading of radiation-induced interstitials into Cu GBs and assessed its effect on recombination reactions with vacancies [31,32].…”
Section: Motivationmentioning
confidence: 99%
See 1 more Smart Citation